2015
DOI: 10.2298/apt1546045g
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties of honeybee pollen enriched acidophilus milk and probiotic yoghurt

Abstract: The aim of this work was to examine the possibility of preparation of acidophilus milk and probiotic yoghurt by processing of milk (1%, 2.8% and 3.2% w/w fat) enriched with honeybee pollen (0.6% w/w). The quality of produced fermented milks was followed by comparing pH value during fermentation and storage time, as well as of lactic acid content and sensory properties during 14 days of storage. Fermentation time was influenced more the type of the starter culture than by honeybee pollen addition or fat level. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
1
2
0
1
Order By: Relevance
“…In addition, when chemical analyses were evaluated, it was found that the addition of pollen caused a decrease in pH and titratable acidity and caused an increase in some minerals (Mo, Cu, Mn, B, Zn, Fe, S, Mg, Ca, K, P). These results confirm the results of the studies in the literature (Küçükçetin, 2008;Yerlikaya, 2014;Lomova et al, 2014;Glušac et al, 2015;Atallah, 2016;Zlatev et al, 2018). On the other hand, considering this study, physicochemical and sensory properties can be compared by adding pollen to yoghurt samples before and after incubation, and by increasing the concentration ratio, sensory properties can be examined at high rates.…”
Section: Conclusion and Recommendationssupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, when chemical analyses were evaluated, it was found that the addition of pollen caused a decrease in pH and titratable acidity and caused an increase in some minerals (Mo, Cu, Mn, B, Zn, Fe, S, Mg, Ca, K, P). These results confirm the results of the studies in the literature (Küçükçetin, 2008;Yerlikaya, 2014;Lomova et al, 2014;Glušac et al, 2015;Atallah, 2016;Zlatev et al, 2018). On the other hand, considering this study, physicochemical and sensory properties can be compared by adding pollen to yoghurt samples before and after incubation, and by increasing the concentration ratio, sensory properties can be examined at high rates.…”
Section: Conclusion and Recommendationssupporting
confidence: 89%
“…The addition of pollen in samples resulted in a decrease in pH level. Küçükçetin (2008), Yerlikaya (2014) and Glušac et al (2015) suggested that the addition of pollen to yogurt and dairy products would decrease the pH level. The findings of the research have reached similar results with the studies conducted in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…Pseudomonas aeruginosa dan Enterococcus faecalis. 6,8,9,10 Adanya aktivitas antibakteri dan kandungan nutrisinya yang tinggi, membuat polen lebah sering ditambahkan dalam berbagai suplemen 11 dan digunakan sebagai ajuvan dalam berbagai terapi. 12,13 Sampai saat ini, belum ada informasi mengenai aktivitas antibakteri polen lebah terhadap Salmonella typhi.…”
Section: Pendahuluanunclassified
“…According to the results of the research made to examine the effects of physico-chemical and microbiological features of yogurts produced by honey, pollen and probiotic yeast, it is identified that there are significant increases in the amounts of oil and protein in yogurt due to the pollen addition [5]. Another study revealed that the probiotic yogurt produced by adding pollen has a positive impact on both physico-chemical and sensorial features [55]. Unfortunately, the positive impact of the addition of pollen in the yogurt on senses of taste and smell is revealed to be not the same in the case of adding the pollen in milk.…”
Section: Pollenmentioning
confidence: 99%